2020
DOI: 10.1136/bmjopen-2019-035216
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on prevalence of metabolic syndrome based on three criteria among adults in Zhejiang province, China: an observational study

Abstract: ObjectivesIn this study, we aimed to estimate the prevalence of metabolic syndrome (MetS) among Chinese adults, describe the disease components and compare utility of the existing international criteria and Chinese diagnostic criteria.Design, setting and participantsA retrospective database analysis was conducted for one hospital in Zhejiang province, China. We analysed data (collected in 2017) from a total of 64 902 participants (37 500 males and 27 402 females), aged between 18 and 97 years, and who met the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…10 The latest national meta-analysis in 2016 estimated the prevalence of MetS in China as 24.5%, 11 but multi-ethnic population here aged ≥20 years showed a lower prevalence of MetS (15.9%) in the study. 12 As to mono-population, 30.0% prevalence of MetS was observed in Han ethnic group aged ≥18 years in Zhejiang province, China, 13 and a study in the Han group in northeast China reported an overall prevalence of MetS as 41.3%. 14 It is clear that the prevalence of MetS in the mono-population higher than that in the multiethnic population and the Chinese Han group is much higher than in other ethnic minorities in China.…”
Section: Introductionmentioning
confidence: 98%
“…10 The latest national meta-analysis in 2016 estimated the prevalence of MetS in China as 24.5%, 11 but multi-ethnic population here aged ≥20 years showed a lower prevalence of MetS (15.9%) in the study. 12 As to mono-population, 30.0% prevalence of MetS was observed in Han ethnic group aged ≥18 years in Zhejiang province, China, 13 and a study in the Han group in northeast China reported an overall prevalence of MetS as 41.3%. 14 It is clear that the prevalence of MetS in the mono-population higher than that in the multiethnic population and the Chinese Han group is much higher than in other ethnic minorities in China.…”
Section: Introductionmentioning
confidence: 98%
“…However, the impact of different definitions of MetS remains diverse. Other definitions are also used to identify individuals with MetS, such as the Iranian definition 7 Chinese Diabetes Society 2013, 8 and the modified World Health Organization (WHO). 9 The JIS (2009) criteria are very similar to those in modified NCEP-ATP III (2005) but it is different with the IDF (2005) in terms of central obesity that needs to be the first and most important criteria of the MetS.…”
Section: Introductionmentioning
confidence: 99%
“…1 Epidemiological studies have reported a high prevalence of MetS worldwide. [2][3][4] This is particularly so for patients with T2DM and hypertension. 4,5 Given the poor prognosis and high all-cause mortality rate of CVD, early assessment of cardiometabolic risks and treatment is important.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] This is particularly so for patients with T2DM and hypertension. 4,5 Given the poor prognosis and high all-cause mortality rate of CVD, early assessment of cardiometabolic risks and treatment is important. 1,4 Identification of MetS is essential for healthcare professionals and patients to address the underlying lifestyle-related risk factors such as sedentary lifestyle, physical inactivity, smoking, and alcohol abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation